Of the young, for the young, by the young - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
'48 hours of radio - per day, please!': this is what young people in Mali want. Information about school life and agriculture, about rural markets, income-generating activities and job opportunities, but also about topics like health and kitchen...